Carbohydrate Catabolism of Selected Strains in the Genus Agrobacterium - Arthur, Larry O. (1975)
Radiorespirometric and enzyme analyses were used to reveal the glucose-catabolizing mechanisms functioning in single strains of seven presumed Agrobacterium species. The Entner-Doudoroff and pentose cycle pathways functioned in A. radiobacter, A. tumefaciens, A. rubi, and A. rhizogenes. Whereas both catabolic pathways were utilized to an almost equal degree in the A. radiobacter and A. tumefaciens strains, use of the Entner-Doudoroff pathway predominated in the A. rubi and A. rhizogenes strains. A. stellulatum catabolized glucose almost solely through the Entner-Doudoroff pathway. In A. pseudotsugae and A. gypsophilae, glucose was metabolized mainly through the Emden-Meyerhof-Parnas pathway; the pentose phosphate pathway was also utilized.